Memorandum of Understanding between the International Development Research Centre and BRAC University (2012) - International Development Research Centre (IDRC); BRAC University (International Development Research Centre (IDRC) and BRAC University, 2013)
1. Project objectives. 2. Recipient. 3. Project leader. 4. Contacts. 5. Availability of centre funds and term. 6. Country approval. 7. Amendment.